Modern Solutions to Pathogenetic Risk Factors Causing Acute Laryngotracheitis - Shakhnoza, Abdukodirova (Journal of Science in Medicine and Life, 2024)
Mixed forms of pathology are combined in nature and are caused by the effects of viruses and bacteria (in this case, often the primary viral infection is primary, and the bacterial component is layered later). The classification is based on the nature of the clinical appearance and morphological (tissue) changes in the affected organs. Discharge: the classic catarrhal form, swelling of the larynx and trachea is observed, but there are no long-term and serious changes; atrophic form, in which the volume of mucous membrane tissue decreases; hypertrophic type, the most dangerous, because it is accompanied by an increase in tissue volume, cyst and pseudotumor changes, can lead to cancer. Laryngotracheitis occurs in adults and children. Men and women get sick equally often. There are no significant gender differences in the course of the disease.